2020
DOI: 10.2147/ott.s253154
|View full text |Cite
|
Sign up to set email alerts
|

<p>FKBP10 Acts as a New Biomarker for Prognosis and Lymph Node Metastasis of Gastric Cancer by Bioinformatics Analysis and in Vitro Experiments</p>

Abstract: To explore the role of FKBP prolyl isomerase 10 (FKBP10) protein in the progression of gastric cancer. Methods: Four independent gastric cancer databases (GSE27342, GSE29272, GSE54129 and TCGA-STAD) were used to identify differentially expressed genes (DEGs). Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis was used to identify the abnormally active pathways in patients with gastric cancer. Univariate Cox regression analysis was used to identify genes with stable prognostic value in gastric cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…[ 38 ] Additionally, FKBP10 is a biomarker for gastric cancer progression and metastasis. [ 39 ] In our study, we found that FKBP10 was upregulated in CRC tissues and may be a potential marker for prognosis. Our results demonstrated that FKBP10 knockout suppressed CRC growth and metastasis.…”
Section: Discussionmentioning
confidence: 68%
“…[ 38 ] Additionally, FKBP10 is a biomarker for gastric cancer progression and metastasis. [ 39 ] In our study, we found that FKBP10 was upregulated in CRC tissues and may be a potential marker for prognosis. Our results demonstrated that FKBP10 knockout suppressed CRC growth and metastasis.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, in the endoplasmic reticulum of fibroblasts, the FKBP10 protein binds to Hsp47 (heat shock protein 47) to promote the synthesis of procollagen and formation of mature collagen molecules, thereby forming a more stable complex to construct extracellular matrix [15,16]. FKBP10 expression is aberrant in a variety of malignancies and is often associated with poor prognosis in patients [17,18]. It has been reported that FKBP10 expression is negatively correlated with the survival rate of lung cancer patients, and the regulative effect of FKBP10 on protein translation sustains the growth of lung cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…A prognostic role has also been reported for some of these genes, both negative ( ERRFI1 ) [ 25 ], and positive ( SLC44A3 ) [ 29 ]. Additionally, several of the differentially expressed genes are proposed to be potential therapeutic targets, such as FAIM2 in small cell lung carcinoma [ 18 ], ERRFI1 in pancreatic carcinoma [ 25 ], RASA4 in triple-negative breast carcinoma [ 53 ], FKBP10 in gliomas [ 7 , 18 ], metastatic gastric carcinoma [ 16 ] and lung carcinoma [ 38 ], and CACNA2D in prostate carcinoma [ 18 ]. Overview of the most interesting genes differentially expressed between the cell-lineage based groups of PitNETs has been presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%